2018
DOI: 10.1055/s-0038-1675333
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Considerations in Liver Transplantation

Abstract: Liver transplantation (LT) has the potential to cure patients with acute and chronic liver failure as well as a number of hepatic and biliary malignancies. Over time, due to the increasing demand for organs as well as improvements in the survival of LT recipients, patients awaiting LT have become sicker, and often undergo the procedure while critically ill. This trend has made the process of preoperative assessment and planning, intraoperative management, and postoperative management even more crucial to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 179 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…Recipients with higher MELD scores are more likely to develop pre-operative complications and have higher rates of ICU utilization and mechanical ventilation. Respiratory complications requiring mechanical ventilation are common among patients with ESLD, and recent studies suggest that preoperative respiratory failure is not a contraindication to OLT with proper patient selection [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Recipients with higher MELD scores are more likely to develop pre-operative complications and have higher rates of ICU utilization and mechanical ventilation. Respiratory complications requiring mechanical ventilation are common among patients with ESLD, and recent studies suggest that preoperative respiratory failure is not a contraindication to OLT with proper patient selection [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional orthotopic liver transplantation (OLT) is complicated and involves a high risk of acid-base imbalance and drastic haemodynamic fluctuations [ 1 ]. Heming [ 2 ] et al emphasized that the intravenous infusion of crystalloids is a key process to ensure tissue perfusion, cell oxygenation and physiological status in OLT patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is the first-line agent to maintain end-organ perfusion pressure, especially in critically ill patients with low systemic vascular resistance. Many centers use it to minimize transfusion volume and fluid administration during the pre-anhepatic and anhepatic phase, and to reduce the occurrence of postreperfusion syndrome during the neohepatic phase of LT (Barjaktarevic et al, 2018). Previous studies have shown that NE-induced, b1-mediated increase in myocardial contractility played a crucial role in increasing the cardiac index of septic, postcardiotomy vasodilatory shock (Nygren et al, 2010;Redfors et al, 2011) and LT (Skytte Larsson et al, 2018) patients.…”
Section: Introductionmentioning
confidence: 99%